The first hundred years: what have we learnt? : A century of museum education at the Ethnographic Museum - Jelavić, Željka (Array, 2019)
The paper addresses the issue of development of educational activities in the Ethno- graphic Museum in Zagreb throughout its first 100 years of activity. During the first years of operation of the Museum educational activities were evident primarily in the work of the curator Mirko Kus-Nikolajev, despite the fact that there was no conceptualised approach to educational activities in the Museum at the time. Several decades later, in the second half of the 20th century a conceptualised approach was formulated by the first museum educators: Aleksandra Sanja Lazarević and Nada Majanović. Today, the educational programme is currently being developed in accordance with the contemporary trends in museum education, which focuses on different groups of museum users and highlights the social responsibility of the Museum.